2016
DOI: 10.1159/000444528
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Diergic Trophic Effects of Estradiol Exposure on Developing Bovine Cerebellar Granule Cells

Abstract: In the mammalian brain, the differentiation of neural cells and the developmental organization of the underlying circuitry are influenced by steroid hormones. The estrogen 17-β estradiol (E2) is one of the most potent regulators of neural growth during prenatal life, synthetized locally from steroid precursors including prenatal testicular testosterone. Estradiol promotes brain differentiation counting sexually dimorphic neural circuits by binding to the estrogen receptors, ER-α and ER-β. The cerebellum has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…Since is well known that many neuronal cell types may be simultaneously present within one layer of motor cortex, it is advisable to generalize model (1) and refer to a more flexible and realistic mixture distribution model (McLachlan and Peel 2004). This approach is recommended by the literature when the information regarding the reference subpopulation from which the sample has been drawn is unavailable; such is our case, where the class to which each examined neuronal cell belongs is unknown.…”
Section: Statistical Analysis Morphometric Features Definitionmentioning
confidence: 99%
“…Since is well known that many neuronal cell types may be simultaneously present within one layer of motor cortex, it is advisable to generalize model (1) and refer to a more flexible and realistic mixture distribution model (McLachlan and Peel 2004). This approach is recommended by the literature when the information regarding the reference subpopulation from which the sample has been drawn is unavailable; such is our case, where the class to which each examined neuronal cell belongs is unknown.…”
Section: Statistical Analysis Morphometric Features Definitionmentioning
confidence: 99%
“…In this context, the intersex bovine freemartin offers an interesting model to study sex differences of the brain and development in translational medicine (Graïc et al 2018). Furthermore, a previous in vitro study performed on this species in our laboratory reported that granule cells of the female cerebellum showed significantly larger morphological values than the corresponding male elements (Montelli et al 2017).…”
Section: Sexual Dimorphism and The Cerebellar Cortexmentioning
confidence: 80%
“…To this effect, morphometric parameters including neuronal size, density or volume may compose a multi-scale view to quantify the distribution of specific neurons (Silvestri et al 2015) and develop new methods to systematically extract useful information from neuroanatomical data (DuBois Bowman et al 2007;Ozaki 2014;Graïc et al 2020, in press). The need for advanced statistical methods and modern techniques for image analysis of neural cells led to several specific studies in our laboratory (Montelli et al 2017;Cozzi et al 2017;Graïc et al 2018).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…As it is well known that steroid hormones influence neurogenesis and dendritic growth on neural cells, these effects may have influenced sexual dimorphism by increasing the overall number and size of neurons within the hypothalamic nuclei, including the VON. A recent paper showed that estrogens exposure exerts a trophic effect on developing bovine granular neurons (Montelli, Suman, Corain, Cozzi, & Peruffo, ). Previous work on estrogen receptors α and β in Cetartiodactyla (including the ovine and the bovine) (Panin, Corain, Montelli, Cozzi, & Peruffo, ; Peruffo, Buson, et al, ; Schaub, Gersting, Keller‐Wood, & Wood, ), suggest that, in freemartins, the brain of the female twin exposed to male androgens undergoes a partial masculinization either through aromatization into estrogens and activation of ER‐α and ER‐β (Kudwa, Michopoulos, Gatewood, & Rissman, ; Roselli, Liu, & Hurn, ), or via the direct effect of androgens on androgen receptors.…”
Section: Discussionmentioning
confidence: 99%